Tinjauan Literatur Kesan Obesiti ke atas Psikososial Remaja (Jurnal Pembangunan Sosial, 2015)
Obesity is a health problem that threatens all aspects of human life. While rising rates of obesity involving adolescents do not show such a drastic increase, this problem should not be underestimated. In addition to grappling with the issue of adolescent development, adolescent obesity is also facing with the problem of physical health, social and psychological caused by obesity. If the issue is not addressed with appropriate intervention, obese adolescent will have the quality of life and well-being of poor and disrupt their functioning in society. Therefore, this paper will try to discuss about the health effects of psychological and social (psychosocial) experienced by obese adolescents based on the literature review and proposed interventions that can be used to help them.